High-speed mass transfer in the W–Cu pseudo-alloy. (1st May 2022) - Nelasov, I.V.; Kartamyshev, A.I.; Boev, A.O.; Kolobov, Yu. R.
Abstract: Tungsten–copper alloys are heat-resistance materials for aerospace industry. Structure stability during processing and exploitation is controlled by the diffusion processes. In particular, the microstructure evolution is determined by the diffusion of copper atoms in tungsten matrix. Several experimental studies report different diffusivity of copper, which can be associated with the discrepancy of activation energy of diffusion depending on the structure of grain boundaries in tungsten. We performed density functional theory calculations of vacancy formation energies, segregation energies, and migration barriers for copper atoms in certain high-angle grain boundaries of special type using nudged elastic band method. Based on this information we calculated the corresponding diffusion coefficients. We found that the diffusivities in the studied grain boundaries exceed the extrapolated experimental data obtained at low temperatures at least by five times. The obtained data on diffusion path help to explain the depth, from which copper is removed during the annealing of the W–Cu alloy at 1500 K. Highlights: We calculated formation energies of high-angle special grain boundaries in tungsten. We calculated migration energies of Cu atoms in grain boundaries in tungsten. We calculated vacancy formation energies in grain boundaries in tungsten. Diffusion path of Cu is closer to the experimental data than previous results.